Analysis of IFT74 as a candidate gene for chromosome 9p-linked ALS-FTD - Momeni, Parastoo; Schymick, Jennifer; Jain, Shushant; Cookson, Mark R; Cairns, Nigel J; Greggio, Elisa; Greenway, Matthew J; Berger, Stephen; Pickering-Brown, Stuart; Chiò, Adriano; Fung, Hon Chung; Holtzman, David M; et al. (BMC neurology, 2006)
A new locus for amyotrophic lateral sclerosis--frontotemporal dementia (ALS-FTD) has recently been ascribed to chromosome 9p. We identified chromosome 9p segregating haplotypes within two families with ALS-FTD (F476 and F2) and undertook mutational screening of candidate genes within this locus. Candidate gene sequencing at this locus revealed the presence of a disease segregating stop mutation (Q342X) in the intraflagellar transport 74 (IFT74) gene in family 476 (F476), but no mutation was detected within IFT74 in family 2 (F2). While neither family was sufficiently informative to definitively implicate or exclude IFT74 mutations as a cause of chromosome 9-linked ALS-FTD, the nature of the mutation observed within F476 (predicted to truncate the protein by 258 amino acids) led us to sequence the open reading frame of this gene in a large number of ALS and FTD cases (n = 420). An additional sequence variant (G58D) was found in a case of sporadic semantic dementia. I55L sequence variants were found in three other unrelated affected individuals, but this was also found in a single individual among 800 Human Diversity Gene Panel samples. Confirmation of the pathogenicity of IFT74 sequence variants will require screening of other chromosome 9p-linked families.